Analisis dan Perancangan Sistem Informasi Direktorat Research & Technology Transfer Binus University - Mahenda Metta Surya; Albert Wongso; Richard Richard (Bina Nusantara University, 2014)
Rapid growth of information technology development as well as increasing level of competition make every company need to establish an information system to support its business process. Research & Technology Transfer Directorate of Binus University is aware of this matter and makes a goal to improve the existing business process and develop a web-based information system that is able to support the existing business process to be more effective and efficient. This study aims to conduct an analysis and a design of information system for Research & Technology Transfer Directorate Binus University that can enhance the existing business process. Research used two methods, firstly data gathering done by conducting field studies and literature reviews, secondly the analysis and design of the system with object-oriented method. The result achieved from this research is a web-based information system that can support Research & Technology Transfer Directorate business process. The conclusion of this research is a new integrated web-based information system that can support and enhance current business process by connecting all parts of the system with the result to make all process more effective and efficient.